Participation in lung cancer screening - Baldwin, David R. (Transl Lung Cancer Res, 2021)
Although there is now strong evidence for the efficacy of low-radiation dose computed tomography in reducing lung cancer mortality, the challenge is to establish screening programmes that have the maximum impact on the disease. In screening programmes, participation rates are a major determinant of the success of the programme. Informed uptake, participation, and adherence (to successive screening rounds) determine the overall impact of the intervention by ensuring the maximum number of people at risk of the disease are screened regularly and therefore have the most chance of benefiting. Existing cancer screening programmes have taught us a great deal about methods that improve participation. Although evidence is emerging for the efficacy of some of those methods in lung cancer screening, there is still much work to do in the specific demographic that is most at risk of lung cancer. This demographic, characterised by higher levels of socioeconomic deprivation, may be less willing to engage with healthcare interventions and present a particular challenge in the process of ensuring informed choice. In this article we review the evidence for improving participation and describe the challenges that need to be addressed to ensure the successful implementation of CT screening programmes.